Perilaku Mahasiswa Poltekkes Kemenkes Mamuju Terhadap Pengelolaan Sampah - Simba, Julia Elisa; Ashari, Agus Erwin; H, Miftah Chairani; Akbar, Fajar (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
Human activities always produce residues, one of which is in solid form which is commonly referred to as solid waste or garbage. One place that has a high potential for waste production in a city is a college or university campus. The waste that is usually generated in educational buildings, such as a campus, is in the form of organic waste, recyclable waste and non-recyclable waste. This study aims to determine the level of knowledge, attitudes and actions of students at the Mamuju Ministry of Health Poltekkes regarding waste management where the number of respondents was 92 level 2 students at the Mamuju Ministry of Health Polytechnic. This research includes descriptive research. Held during June 2023 at the Mamuju Ministry of Health Polytechnic on the Mamuju-Kalukku axis road Km.16 Tadui, West Sulawesi. Based on the research results obtained, it shows that the level of knowledge value of Mamuju Ministry of Health Polytechnic students is low (33.7%) regarding waste management. While the level of attitudes and actions of the Mamuju Ministry of Health Poltekkes students is the attitude value (81.5%) and the action value (95.7%). The conclusion of this study is that the knowledge of students at the Mamuju Health Polytechnic regarding waste management is still relatively low, while the attitudes and actions of students regarding waste management are high. It is recommended to conduct counseling for each department regarding waste management to increase students' knowledge of waste management, increase awareness in sorting waste based on its characteristics.